2012
DOI: 10.1261/rna.032045.111
|View full text |Cite
|
Sign up to set email alerts
|

Rrp6 is recruited to transcribed genes and accompanies the spliced mRNA to the nuclear pore

Abstract: Rrp6 is an exoribonuclease involved in the quality control of mRNA biogenesis. We have analyzed the association of Rrp6 with the Balbiani ring pre-mRNPs of Chironomus tentans to obtain insight into the role of Rrp6 in splicing surveillance. Rrp6 is recruited to transcribed genes and its distribution along the genes does not correlate with the positions of exons and introns. In the nucleoplasm, Rrp6 is bound to both unspliced and spliced transcripts. Rrp6 is released from the mRNPs in the vicinity of the nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…However, recent evidence has shown that Rrp6 indeed can bind to RNAs without exerting its ribonuclease function. In Chironomus tentans, Rrp6 binds to nascent transcripts before splicing and accompanies the spliced mRNA to the nuclear pore, where it is released from the mRNPs before nucleo-cytoplasmic translocation (Hessle et al, 2012). It is unknown whether such RNA retention requires a physical association between Rrp6 and other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown that Rrp6 indeed can bind to RNAs without exerting its ribonuclease function. In Chironomus tentans, Rrp6 binds to nascent transcripts before splicing and accompanies the spliced mRNA to the nuclear pore, where it is released from the mRNPs before nucleo-cytoplasmic translocation (Hessle et al, 2012). It is unknown whether such RNA retention requires a physical association between Rrp6 and other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the RNA surveillance machinery, including the TRAMP complex and the nuclear exosome, apparently retain or degrade aberrant or non-functional RNA species in the vicinity of the NPCs (13,16). Moreover, human Nup98 regulates degradation of the p21 CIP1 mRNA by the exosome, and Rrp6 is recruited to nascent transcripts and is then released from mRNPs near the NPCs in Chironomus tentans (48,55). These findings indicate that NPCs could provide a platform for mRNA degradation, and/or that the NPCs may regulate whether mRNPs are exported or degraded.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this end, an overexpressed tagged version of Rrp6 was shown to associate with chromatin of yeast protein coding genes using whole open reading frame cDNA mircroarrays (11). In Drosophila , it was demonstrated that certain exosome subunits associate with at least some actively transcribed genes (12,13) and may be recruited to chromatin through interaction with RNA polymerase II (Pol II) elongation factors Spt5 and Spt6 (14). Nevertheless, a high-resolution genome-wide study of exosome chromatin association has yet to be performed in any organism.…”
Section: Introductionmentioning
confidence: 99%